(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2026)
This paper illustrates a convoluted exploration of the portrayal of hegemonic masculinity in Begum Rokeya Sakhawat Hossain’s Padmarag. Through the depiction of diverse male characters in Padmarag, Rokeya deconstructs the perception of universal male privilege in patriarchal society and challenges the monolithic and unidimensional representation of masculinity. Through deploying Connell’s theory of hegemonic masculinity and an intersectional lens, this paper scrutinizes how socio-cultural, financial, and colonial aspects frame and situate men within patriarchy. The paper illuminates that through Padmarag, Rokeya unveiled the fluid nature of masculinities. It also extensively portrayed how Rokeya challenged the colonial paradigm that situates Western men as sophisticated and reveals the moral and social fraudulence immanent in colonial masculinities in Padmarag. This paper endeavors to enhance the academic discourse by highlighting new discernments about Padmarag, which focuses on the fluid, multifaceted, and heterogeneous nature of masculinity in colonial Bengal. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 70(2), December 2025, pp. 143-153